2022
DOI: 10.1002/ange.202210211
|View full text |Cite
|
Sign up to set email alerts
|

In‐Situ‐Analyse Anionischer Koordinationspolymerisationen durch Elektrosprayionisations‐Massenspektrometrie

Abstract: Anionische Koordinationspolymerisationen verlaufen über hochreaktive Zwischenstufen, deren in situ‐Analyse schwierig bleibt. Hier zeigen wir, dass Elektrosprayionisations‐Massenspektrometrie eine vielversprechende Methode ist, um detaillierte Informationen über den Polymerisationsprozess zu erhalten. Für die durch CoCl2/RLi (R=Me, nBu, tBu, Ph) initiierte Polymerisation von 1,3‐Dienen initiiert beobachten wir die wachsenden Ketten direkt und charakterisieren die aktiven Cobalt‐Zentren durch Fragmentierungsexpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The correction factor X cor is defined as the ratio of the true molecular weight ( MW calc ) and the molecular weight determined via standard ECC merge ( MW det ). In the current study, we use ECC merge for all of the compounds because we found no further separation into compact spheres (CS), expanded discs (ED), and dissipated spheres and ellipsoids (DSE) is required, and the most serious impact is due to the heavy atom …”
mentioning
confidence: 99%
“…The correction factor X cor is defined as the ratio of the true molecular weight ( MW calc ) and the molecular weight determined via standard ECC merge ( MW det ). In the current study, we use ECC merge for all of the compounds because we found no further separation into compact spheres (CS), expanded discs (ED), and dissipated spheres and ellipsoids (DSE) is required, and the most serious impact is due to the heavy atom …”
mentioning
confidence: 99%